Modeling of population growth for the European bison Bison bonasus (European Bison Conservation Newsletter, 2012)
The paper presents first attempt of modeling the population of European bison kept at Island of Bornholm. The tool FITOM v.1 was created and compared with results of one commonly used programs RAMAS. It was found that results obtained in this way were underestimated. Following this early pilot study the program will be developed.
Keywords: modeling; Island of Bornholm; Almindingen; European bison; introduction